(untitled) (World Bulletin of Public Health, 2023)
According to the literature, in recent years, the relationship of overweight and obesity with vitamin D deficiency has been published very often. This study was conducted at the TMA in the general hospital in the department of 2 therapy and endocrinology. 85 women with exogenous constitutional obesity and 30 women of the control group with normal body weight were examined. The results showed that the higher the BMI, the more pronounced the vitamin D deficiency. In addition, these women had a high level of insulin and an indicator of insulin resistance. Also, a negative correlation was found between the content of vitamin D and some parameters of the study - insulin in the blood and the state of insulin resistance.